HPV vaccination coverage, hesitancy, and barriers: Insights from a serial cross-sectional study in Shanghai, China (2019–2024) - Mengdi Ji; Zhuoying Huang; Han Yan; Jia Ren; Abram L. Wagner; Xiaodong Sun; Matthew L. Boulton (Human Vaccines & Immunotherapeutics)
Cervical cancer is the fourth most common cancer among women globally and a significant public health challenge in China, which accounts for nearly 18% of global cervical cancer cases. The HPV vaccine is a proven intervention for preventing high-risk HPV infections and associated cancers. This serial cross-sectional study conducted in Shanghai, China, in 2019 and 2024 analyzed changes in HPV vaccination rates and vaccine hesitancy. Multivariable logistic regression was used to assess the associations between HPV vaccination, general vaccine hesitancy, and HPV-specific vaccine hesitancy, adjusting for sociodemographic factors. The Population Attributable Fraction (PAF) quantified the proportion of non-vaccination attributable to these factors. In 2019 and 2024, two waves of data were collected from 1,037 and 1,450 parents, respectively. Results showed an increase in HPV vaccination from 6% to 30% during the study period, primarily among women aged 18 and older, while coverage among the WHO target group (girls aged 9–14) remained low at 8%. Parents with HPV-specific vaccine hesitancy were 75% less likely to vaccinate their daughters (OR = 0.25, 95% CI: 0.11–0.56), while general vaccine hesitancy reduced vaccination likelihood by 94% (OR = 0.06, 95% CI: 0.00–0.89). PAF analysis indicated that HPV-specific vaccine hesitancy contributed to 24% of non-vaccination cases, higher than general vaccine hesitancy (10%). These findings highlight the critical need for targeted interventions addressing HPV-specific barriers, improving education about vaccination timing and options, and reducing logistical obstacles to align with global cervical cancer elimination goals.